2002
DOI: 10.1139/t02-054
|View full text |Cite
|
Sign up to set email alerts
|

Transition of soil friction during suction pile installation

Abstract: A series of laboratory model tests on the suction pile installation in sand have been conducted to obtain the relationship between the applied suction pressure inside the pile and the resulting pile penetration. The relationships have been used to estimate the mobilized soil strength during the pile installation. This reduction in the soil strength due to the applied suction pressure is described as a function of a nondimensional parameter to characterize the variation and transition of the soil strength durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The considerable costs of field trials also limit the variations of different installation parameters during tests. To overcome the cost problem, many installation studies have been conducted by means of cheaper and more flexible smallscale model tests (Allersma et al, 1997;Cho et al, 2002;Allersma, 2003;Tran et al, 2004), where changes in installation conditions can be made easily. However, interpretation of suction pressures during installation, either in the field or in model studies, has not been addressed adequately so far.…”
Section: Introductionmentioning
confidence: 99%
“…The considerable costs of field trials also limit the variations of different installation parameters during tests. To overcome the cost problem, many installation studies have been conducted by means of cheaper and more flexible smallscale model tests (Allersma et al, 1997;Cho et al, 2002;Allersma, 2003;Tran et al, 2004), where changes in installation conditions can be made easily. However, interpretation of suction pressures during installation, either in the field or in model studies, has not been addressed adequately so far.…”
Section: Introductionmentioning
confidence: 99%
“…These variations of the suction pressure during installation and the positive pressure during retrieval have been observed from previous field tests (5,6). The plots shown in Figures 8 and 9 will be used in the future to further validate the analytical solutions for the suction pile installation and retrieval already developed by the authors (4,6). The analytical solutions use the concept of the mobilized soil strength ratio.…”
Section: Test Resultsmentioning
confidence: 97%
“…The mobilized soil strength ratio is the soil strength necessary for the equilibrium between the externally applied force through suction/positive pressure and the pile resistance divided by the fully available soil strength. Previous field and laboratory model tests (1,(3)(4)(5)(6) indicated that the mobilized soil strength ratio increases during installation as the pile penetrates into the sea floor and becomes larger as the pile diameter gets smaller. However, during retrieval, the mobilized soil strength ratio increases as the pile is pulled out and becomes larger as the pile diameter increases.…”
Section: Test Resultsmentioning
confidence: 99%
“…Complete details of the suction pile design, considering the external loads and safe installation, are beyond the scope of this paper. They are well described in references [4,5,6,7,8,9]. From September through late November 2004, four suction piles were fabricated at a location adjacent to the wharf near the test site.…”
Section: Suction Pile Details and Installationmentioning
confidence: 99%